On Assemblages and Surveillantization: Thinking and Rethinking Surveillance Theory - Haggerty, Kevin D. (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
It has been over a quarter of a century since I wrote The Surveillant Assemblage with my colleague Richard Ericson. In it, we advance a theoretical model for understanding key aspects of surveillance, aiming to move beyond portraying it as a form of totalitarian “Big Brother” or Foucauldian panopticism. Inspired by Gilles Deleuze and others, we detailed how surveillance operates by integrating heterogeneous practices and technologies, contributing to the production, combination, and movement of data flows. Among other dynamics, we accentuated fluidity and processes of emergence, integration, and the proliferation of data doubles. Scholars in fields as different as media studies, criminology, anthropology, critical race studies, data science, gender studies, architecture, law, and sociology have applied the model or debated its relevance to a wide range of empirical settings. But no model is fully comprehensive, and developments in surveillance now move rapidly. As such, it has been invigorating to revisit this article and rethink how to adequately theorize surveillance. My comments here set out to do three things. First, I use this opportunity to briefly introduce the notion of “surveillantization,” which I see as a valuable way to conceive of some of the “big picture” developments and trajectories in surveillance. Second, I return to the surveillant assemblage to offer a few thoughts on the commentators’ essays in this forum. The concluding section is a coda that provides background on writing the original surveillant assemblage article. It offers a glimpse into one small part of the early history of surveillance studies.